Randomised clinical trial: exploratory phase 2 study of ONO‐2952 in diarrhoea‐predominant irritable bowel syndrome. Issue 1 (7th November 2016) - Whitehead, W. E.; Duffy, K.; Sharpe, J.; Nabata, T.; Bruce, M.
Summary: Background: ONO‐2952 is a novel and selective inhibitor of translocator protein 18 kDa that reduces stress‐induced defecation and visceral hyperalgesia in rat models. Aim: To evaluate the efficacy and safety of ONO‐2952 in females with irritable bowel syndrome with diarrhoea in an exploratory proof‐of‐concept study. Methods: A randomised, double‐blind, placebo‐controlled study was conducted at 49 US centres. Two hundred subjects with irritable bowel syndrome with diarrhoea (Rome III criteria) were randomised to ONO‐2952 20 mg, or 60 mg, or placebo. Subjects recorded irritable bowel syndrome symptoms daily during a 2‐week baseline period, the 4‐week treatment period and for 4 weeks post‐treatment. The co‐primary endpoints were change from baseline to week 4 in abdominal pain, stool consistency and stool frequency. Results: Improvements in irritable bowel syndrome symptoms were seen with ONO‐2952 over placebo in per‐protocol analyses for all three co‐primary endpoints, but these did not reach statistical significance at the 5% level. The largest improvement was seen with ONO‐2952 60 mg. ONO‐2952 was well tolerated with a safety profile similar to that of placebo. Most adverse events were mild or moderate in severity and not treatment related. Conclusion: ONO‐2952 showed evidence of clinical efficacy in reducing irritable bowel syndrome‐related symptoms in female subjects with irritable bowel syndrome with diarrhoea, and further evaluation is, therefore, warranted to assess its potential as a treatment for irritable bowel syndrome with diarrhoea (NCT01844180). Abstract : Linked Content This article is linked to Nee and Lembo, and Whitehead et al papers. To view these articles visithttps://doi.org/10.1111/apt.13920 andhttps://doi.org/10.1111/apt.13957 .